Malignant Transformation Rate in Patients Presenting Oral Epithelial Dysplasia: Systematic Review and Meta-Analysis. (4th November 2015) - Shariff, Jaffer A.; Zavras, Athanasios I.
Abstract : Objective . To perform a systematic review and meta-analysis on studies that assess malignant transformation rates (MTR) of oral epithelial dysplasia. Materials and Methods . This review was planned and conducted in accordance with the meta-analysis of observational studies in epidemiology (MOOSE) guidelines. PubMed, EMBASE, Google Scholar, and Cochrane databases were screened to identify observational studies. Quality assessments were completed by two reviewers independently using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Pooled-malignant transformation rate (MTR) in person years, subgroup, sensitivity, and publication bias analysis were calculated using STATA 13.0 and Comprehensive Meta-Analysis software. Results . Sixteen observational cohort studies were identified with a total of 3708 participants from Asia, North America, and Europe. Analysis showed a MTR of 10.5% (pooled-MTR: 10.5, 95% CI: 3.7 to 17.3; fixed effect model, I 2 = 0.0 %;Q -value = 2.389;p > 0.05 ) among patients with histologically confirmed oral epithelia dysplasia undergoing long-term follow-up. Higher MTR in person year were seen among the sever dysplastic cases (pooled-MTR: 14.4%, 95% CI: 5.3% to 23.5%), studies published in Europe (pooled-MTR: 12.6%, 95% CI: 8.0% to 24.3%), and retrospective studies (pooled-MTR: 11.0%, 95% CI: 2.2% to 19.9%). Conclusion . These studies show that oral epithelial dysplasia has a significant high rate of transformation to cancer.